Modern Art in the Common Culture. - Crow, Thomas (London New Haven : Yale University Press London Yale University Press New Haven, 1996)
Must avant-garde art hold itself apart from the values and beliefs widely held in the common culture ? Must advanced artists always be the symbolic adversaries of the ordinary citizen ? The questions have dominated, even paralyzed the modern art world, particulary in recent years when perceived elitism and imposed canons of taste have come under fire from all sides. In this stimulating book, a prominent art historian shows that the links between advanced art and modern mass culture have always been robust, indeed necessary to both. Thomas Crow focuses on the continual interdependence between the two phenomena, providing examples that range from Paris in the mid-nineteenth century to the latest revivals of Conceptual art in the 1990s.
Ader, Bas Jan ; Asher, Michael ; Bleckner, Ross ; D'Arcangelo, Christopher ; Denny, Robyn ; Goya, Francisco ; Graham, Dan ; Haacke, Hans ; Halley, Peter ; Holmes, Andrew ; Kiefer, Anselm ; Klimt, Gustav ; Koons, Jeff ; Lemieux, Annette ; Levine, Sherrie ; Louis, Morris ; Manet, Edouard ; Matta-Clark, Gordon ; Monet, Claude ; Picasso, Pablo ; Pollock, Jackson ; Richter, Gerhard ; Rosler, Martha ; Serra, Richard ; Seurat, Georges ; Steichen, Edward ; Sturtevant, Elaine ; de Vlaminck, Maurice ; Wall, Jeff ; Warhol, Andy ; Williams, Christopher
Engels
boek
Keywords: 19de eeuw; 20ste eeuw